2011
DOI: 10.1108/13552551111174729
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of retaining and maintaining knowledge in university technology transfer processes

Abstract: PurposeThis paper focuses on the university science park incubator element of the technology transfer process where knowledge in a variety of forms needs to be retained and maintained. The aim is to investigate the networking competencies of stakeholders involved in the university technology transfer process using absorptive capacity theory to explore how knowledge is externally retained and maintained through these network relations.Design/methodology/approachThis paper undertakes an inductive theory building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Knowledge is responsible for creating wealth and economic growth (Muscio et al, 2013), and is recognised as a key factor in the process of innovation and TT (Miller et al, 2011). The TT process is essentially the application of knowledge (Gibson and Smilor, 1991).…”
Section: Knowledge and Technology Transfermentioning
confidence: 99%
“…Knowledge is responsible for creating wealth and economic growth (Muscio et al, 2013), and is recognised as a key factor in the process of innovation and TT (Miller et al, 2011). The TT process is essentially the application of knowledge (Gibson and Smilor, 1991).…”
Section: Knowledge and Technology Transfermentioning
confidence: 99%
“…The importance of technology transfer showed by Ng et al (2012) stated that dynamic process from capability development will improve technology transfer in domestic workers compared with its foreign development. Miller (2011), then, showed that the development and maintenance of network relationship can significantly improve the knowledge development and retention in technology transfer process. Knowledge is recognized as important input in innovation and technology transfer process (Reychav and Weisberg in Miller et al (2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Miller (2011), then, showed that the development and maintenance of network relationship can significantly improve the knowledge development and retention in technology transfer process. Knowledge is recognized as important input in innovation and technology transfer process (Reychav and Weisberg in Miller et al (2011). Therefore, the usage of absorbent capacity theory to explore the role of proper importance and relationship in defending knowledge is still relevant (McAdam et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, 60% of the research production is the responsibility of governmental section (TSI, 2013). Currently, the interaction between the technology owners and technology transferees is absent, only the transfer level which focuses on machines and equipment than knowledge transfer, is present (Miller et al, 2011). Numerous R&D transfers have not been successful because the nature of innovation itself, which is uncertain and difficult to predict, especially so for radical innovation (Herath & Bremser, 2005).…”
Section: Introductionmentioning
confidence: 99%